Teachers’ Talk of a Walk they Don’t Stride: A Case Study of Education Student Teachers’ Perspectives on Hookah Smoking - Ghamrawi, Najah (Advances in Social Sciences Research Journal, 2021)
Hookah smoking is widely spreading among Lebanese adolescence. The aim of this study was to investigate the perspectives of prospective student teachers pertaining to hookah smoking to determine their readiness to educate their future students in what relates to the dangers of smoking. The sample consisted of education sophomore student teachers (N=53), at the Education Faculty of one university in Lebanon. Participants constituted of the students enrolled in two educational psychology classes taught by the researcher. The topic was not part of what is being taught to students at the university. The e-survey obtained information on participants’ demographics, hookah smoking awareness, and their educative perspectives on hookah smoking. The study used mixed methods employing an 18-item survey on hookah smoking, alongside a semi structured heterogeneous focus group interview with six student teachers; two who were identified respectively as: hookah smokers, non-smokers, semi-smokers, and all were selected randomly from the pool of participants. Findings suggest that education student teachers have dispersed and unbalanced educative perceptions on hookah smoking. The study recommends that an efficient Lebanese anti-smoking awareness program should highly emphasize targeting the college student teachers, who are at the future front line with the youthful upcoming generation, and thus can highly affect their awareness pertaining to smoking in general, and hookah smoking in specific.